Pests and diseases on cowpea in Uganda: Experiences from a diagnostic survey - Adipala, E.; Omongo, C.A.; Sabiti, A.; Obuo, J.E.; Edema, R.; Bua, B.; Atyang, A.; Nsubuga, E.N.; Ogenga-latigo, M.W. (African Crop Science Journal, 1999)
A diagnostic survey (DS) using a questionnaire covering 525 farm households was conducted in 1993/94 to determine the status of cowpea (Vigna unguiculata L. Walp) and its production constraints in Uganda. Subsequent on-farm assessments were made during the two rainy seasons of 1994 to verify and quantify the survey information. Additionally, on-station trials were conducted to address issues arising from the information. Insect pests, low plant population densities, poor weed management and labour bottlenecks are the most important constraints to cowpea production in Uganda. Insect pest damage, particularly by bruchids, is most important. Research to develop integrated pest management (IPM) strategies based on the finding of this study are in progress.
Keywords: Farmer perception; Integrated pest management; On-farm surveys; Production costs; Profitability; Uganda; Vigna unguiculata